In the equation ln x=-2, x is equal to [tex]e^{-2}[/tex]
We have been asked to find x in ln x = -2
⇒ ln x = -2
⇒ x = [tex]e^{-2}[/tex]
Thus, x = [tex]e^{-2}[/tex] in the equation ln x=-2
To solve linear equations, utilize the steps that are provided below.
Lets take an example of solve z for 7z – (3z – 4) = 12
Here is no multiplication or division, so this will be easy to solve
⇒ 7z – (3z – 4) = 12
⇒ 7z – 3z + 4 = 12
⇒ 4z = 12 – 4
⇒ 4z = 8
⇒ z = 8/4
⇒ z = 2
See, that was so simple, using the mentioned methods, every linear equation can be solved easily.
Learn more about linear equations
https://brainly.com/question/14323743
#SPJ4